Pengaruh Orientasi Pasar dan Orientasi Kewirausahaan Terhadap Inovasi Produk dan Keunggulan Bersaing UMKM Jenang di Kabupaten Kudus - Muhamad Zidni Syukron; Ngatno Ngatno (Jurnal Administrasi Bisnis, 2016)
The company's success to maintain the sustainability of their products sales lies in the ability to have a strategy or innovative thinking by seeing on market orientation and entrepreneurial orientation, and having a strong competitive advantage. This research is conducted  to determine  the  influence  of market orientation and entrepreneurial orientation toward product innovation and competitive advantage in Jenang Micro, Small and Medium Enterprises (SMEs) of Kudus Regency. This type of research is explanatory research. The sampling techniques used total sampling that is overall Jenang SMEs owner of Kudus Regency. The respondents in this research totaled 43 respondents. Collecting data used questioner, with score start from 1 (very disagree) to 5 (really agree). This research was also using Path analysis techniques supported by SPSS (Statistical Package for Social Science) software version 20.3. The validity test, reliability test, coefficient of correlation test, coefficient of determination test, linear and multiple regression, significance test (t and F test) and Sobel method beforehand. The results showed that all independent variables in this study had a significant influence on the dependent variable, either partially or simultaneous, product innovation acts as a partial mediating variable, that indicates an indirect effect of variables of market orientation and entrepreneurial orientation on competitive advantage.